The ticking time bomb in lifestyle-related diseases among women in the Gulf Cooperation Council countries; review of systematic reviews - Mashael K. Alshaikh; Filippos T. Filippidis; Hussain A. Al-Omar; Salman Rawaf; Azeem Majeed; Abdul-Majeed Salmasi (BMC, 2017)
Abstract Background This study aims to review all published systematic reviews on the prevalence of modifiable cardiovascular disease risk factors among women from the Gulf Cooperation Council countries (GCC). This is the first review of other systematic reviews that concentrates on lifestyle related diseases among women in GCC countries only. Method Literature searches were carried out in three electronic databases for all published systematic reviews on the prevalence of cardiovascular disease risk factors in the GCC countries between January 2000 and February 2016. Results Eleven systematic reviews were identified and selected for our review. Common reported risk factors for cardiovascular disease were obesity, physical inactivity, diabetes, metabolic syndrome and hypertension. In GCC countries, obesity among the female population ranges from 29 to 45.7%, which is one of the highest rates globally, and it is linked with physical inactivity, ranging from 45 to 98.7%. The prevalence of diabetes is listed as one of the top ten factors globally, and was reported with an average of 21%. Hypertension ranged from 20.9 to 53%. Conclusions The high prevalence of lifestyle-related diseases among women population in GCC is a ticking time bomb and is reaching alarming levels, and require a fundamental social and political changes. These findings highlight the need for comprehensive work among the GCC to strengthen the regulatory framework to decrease and control the prevalence of these factors.